Liver Tissue Regeneration using Nano Silver impregnated Sodium Alginate/PVA Composite Nanofibres - Manikandan G; Yuvashree M; Sangeetha A; Bhuvana K P; Sanjay K Nayak (Ital Publication, 2020)
Liver regeneration is a highly organized tissue regrowth process and is the most important reaction of the injured liver. The present study endeavors towards the preparation and characterization of nanoporous Sodium Alginate (SA)/ Poly Vinyl Alcohol (PVA) composite, nanofibrous scaffolds coated with silver (Ag) nanoparticles for hepatocellular regeneration.  Chitosan based Silver nanoparticles possess high antibacterial activity has been preferred in the scaffold preparation to improve the antibacterial properties. The structural characterization of Ag Nanoparticles revealed the amorphous nature with an average particle size of 300 nm. Nanofibres (Scaffolds) were prepared by electrospinning SA/PVA solution at a voltage of 18-25 kV and Ag NPs were coated on it for antibacterial activity. Invitro studies denoted the growth of nitro compounds, amides and collagen which are the major constituents of liver tissue.